2019
DOI: 10.1038/s41598-019-40358-3
|View full text |Cite
|
Sign up to set email alerts
|

Iws1 and Spt6 Regulate Trimethylation of Histone H3 on Lysine 36 through Akt Signaling and are Essential for Mouse Embryonic Genome Activation

Abstract: The mRNA processing and export factor, Iws1, interacts with the histone H3/H4 chaperone, Spt6 (Supt6 in mouse gene ontology) and recruits the lysine methyltransferase, Setd2, to chromatin to regulate H3K36me3. This recruitment is known to be crucial for pre-mRNA splicing and Iws1 has been shown to interact with REF1/Aly to mediate mRNA export. However, the role of this complex has not yet been examined in embryonic development. Here, we show that knockdown of either Iws1 or S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…Given previous studies that suggested a role for Spn1 in H3K36 methylation ( 3 , 5 , 14 ) and the change we observed in Set2 recruitment after Spn1 depletion (Figure 4E - G ), we used ChIP-seq to measure the genome-wide occupancy of H3K36me2 and H3K36me3 in Spn1-depleted and non-depleted conditions. In these experiments, we also included analysis of H3K4 trimethylation (H3K4me3), given the genetic relationship between Spn1 and the enzymes required for the methylation and demethylation of H3K4 ( 21 , 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given previous studies that suggested a role for Spn1 in H3K36 methylation ( 3 , 5 , 14 ) and the change we observed in Set2 recruitment after Spn1 depletion (Figure 4E - G ), we used ChIP-seq to measure the genome-wide occupancy of H3K36me2 and H3K36me3 in Spn1-depleted and non-depleted conditions. In these experiments, we also included analysis of H3K4 trimethylation (H3K4me3), given the genetic relationship between Spn1 and the enzymes required for the methylation and demethylation of H3K4 ( 21 , 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since both Spn1 and H3K36 methylation have been previously implicated in splicing ( 3 , 5 , 85–89 ), we looked for changes in splicing efficiency after Spn1 depletion by using our RNA-seq data to estimate intron retention (see Materials and Methods). We observed a general tendency for increased intron retention after Spn1 depletion (Figure 7A ), particularly in ribosomal protein transcripts, whose high expression levels gave us greater power to detect changes in intron retention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Components of the RNApII elongation complex interact with histones and this complex also plays important roles in pre-mRNA splicing (reviewed in [19]). The yeast orthologue of Elof1, Elf1, interacts with Iws1 (Spt1) to facilitate histone H3K36 trimethylation (H3K36me3) modification, and recent studies show that Iws1 is also essential for early murine development [20, 21]. In higher eukaryotes H3K36me3 is linked to alternative splicing through the recruitment of polypyrimidine tract-binding protein (PTB) [22, 23].…”
Section: Resultsmentioning
confidence: 99%
“…splicing-related genes, such as SRSF7, HNRNPA2B1, and IWS1(Despic et al, 2017;Kasowitz et al, 2018;Oqani et al, 2019), had vital effects on early embryonic development. Moreover, some biological process related to embryonic development have occurred in advance from morula to early blastocyst in PA, such as positive regulation of kidney development, retina development in cameratype eye, and inner ear receptor cell differentiation.…”
mentioning
confidence: 99%